Heat Capacity and Thermodynamic Property of Lithium Pentaborate Pentahydrate - Wanjing Cui; Long Li; Yafei Guo; Sisi Zhang; Tianlong Deng (Journal of Chemistry)
The heat capacity of lithium pentaborate pentahydrate has been measured using an adiabatic calorimeter at the temperature from 297 to 375 K. No phase transition and thermal anomalies were observed. The molar heat capacity of LiB5O8·5H2O can be expressed as Cp,m (J·mol−1·K−1) = 396.79376 + 35.87528 [T-(Tmax+Tmin)/2]/[(Tmax-Tmin)/2] + 0.16494[T-(Tmax+Tmin)/2]/[(Tmax-Tmin)/2]2 + 8.3083[T-(Tmax+Tmin)/2]/[(Tmax-Tmin)/2]3, where T is the temperature in Kelvin, Tmax=375 K, and Tmin=297 K. The thermodynamic functions of (HT-H298.15), (ST-S298.15), and (GT-G298.15) of LiB5O8·5H2O are obtained via the molar heat capacity at the temperature of 5 K intervals.